Prioritizing Higher Education Facilities Using TOPSIS Based on Student Preferences - Sari, Mutiara Novita; Adya, Rahel Saffana; Aini, Qurrotul (Journal of Information System and Informatics, 2025)
This research aims to prioritize campus facilities for development based on student preferences using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. Recognizing the critical role of facilities in enhancing student success and retention, this study evaluates key criteria such as needs, comfort, current conditions, accessibility, and frequency of use. Data were collected through a random sampling survey involving 98 active students, determined using Slovin's formula with a 10% margin of error. The analysis identifies WiFi as the top priority for improvement, followed by toilets and lifts. This research highlights how TOPSIS has been applied effectively in decision-making processes within education and facility management, offering a structured approach for optimizing resource allocation.